PENGARUH ABU SERBUK KAYU SEBAGAI SUBSTITUSI SEBAGIAN SEMEN DAN BAHAN TAMBAH BESTMITTEL TERHADAP KUAT TEKAN BETON - Sri Devi Devi Pangulu; Nurhayati Doda; Andi Sahrul Hidayat (Program Studi Teknik Sipil FT UNS, 2025)
This study examines the effect of adding sawdust ash as a partial cement substitution and Bestmittel additives on the mechanical properties of concrete, especially compressive strength and initial and final setting times. The method used is a laboratory experiment with variations in concrete mixtures containing sawdust ash of 1% to 5% and the addition of Bestmittel of 0.4% of the weight of cement. The compressive strength test results at the age of 14 days showed that the minimum compressive strength value of 19.08 MPa was obtained in a mixture with a 2% sawdust ash substitution. Meanwhile, the setting time test showed that adding sawdust ash tended to slow down the setting process. The mix with 1% sawdust ash had an initial setting time of 60 minutes and a final setting time of 120 minutes, while the mixture with 5% sawdust ash experienced an increase in the initial setting time to 77 minutes and the final setting time to 150 minutes. Thus, the use of sawdust ash and Bestmittel affects the initial performance of concrete, both in terms of strength and hardening time.Keywords: bestmittel; compressive strength; concrete; sawdust ash; setting time.